Raspailia (Raspaxilla) bouryesnaultae, a new name for Brazilian Raspaxilla elegans Boury-Esnault, 1973 (Demospongiae, Poecilosclerida, Raspailiidae) with a redescription and a new record - Lerner, Cléa; Carraro, João L.; van Soest, Rob (Zootaxa, 2006)
The combination Raspailia (Raspaxilla) elegans sensu Boury-Esnault, 1973 is precoccupied by Raspailia elegans Lendenfeld,1887 (Porifera, Poecilosclerida, Raspailiidae). A new name for this Brazilian shallow-water species is proposed, Raspailia (Raspaxilla) bouryesnaultae n.n., and the species is redescribed based on a skeleton slide from the holotype and additional material freshly collected from the coast of Santa Catarina state. The distribution is now expanded to encompass the area from 22º to 27°S, in southeastern Brazil.